Dinamika Kelompok Tani Desa Air Terbit Kecamatan Tapung Kabupaten Kampar - Andriko '; Roza Yulida; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the level of farmer group dynamics and determine the strategy that is done in a dynamic farmer groups. Sampling was done intentionally, in which 36 people used as respondents from the three groups of farmers in the village of Air Terbit. The results of this study indicate that the rate is determined based on the analysis of the dynamics farmer groups SLR in the village of Air Terbit have moderate criteria with a score of 1.93, it can be seen from the moderate or lack of effort in growing group activities, participation, effectiveness of group responsibility, norms, and sanctions on the group, resulting in a lack of development and building of farmer groups and SWOT analysis determined based strategy in the dynamic group that is an increase of information through a group that supports the promotion of enterprise inputs, farmer group achievement awards, good administration and the right, facilitating the group in order to carry out the functions and good job, get coaching and become better maintenance group, have a strong cohesiveness, conducive atmosphere, adequate pressure, the effectiveness of both groups and improve the existing human resource education through regular training in farmer groups. Keywords: Dynamics, Farmer groups, Strategy